“Cap” Cornish, Indiana Pilot - Ingraham, Ruth Ann (Purdue University Press, 2014)
Clarence “Cap” Cornish was an Indiana pilot whose life spanned all but five years of the Century of Flight. Born in Canada in 1898, Cornish grew up in Fort Wayne, Indiana. He began flying at the age of nineteen, piloting a “Jenny” aircraft during World War I, and continued to fly for the next seventy-eight years. In 1995, at the age of ninety-seven, he was recognized by Guinness World Records as the world’s oldest actively flying pilot. The mid-1920s to the mid-1950s were Cornish’s most active years in aviation. During that period, sod runways gave way to asphalt and concrete; navigation evolved from the iron rail compass to radar; runways that once had been outlined at night with cans of oil topped off with flaming gasoline now shimmered with multicolored electric lights; instead of being crammed next to mailbags in open-air cockpits, passengers sat comfortably in streamlined, pressurized cabins. In the early phase of that era, Cornish performed aerobatics and won air races. He went on to run a full-service flying business, served as chief pilot for the Fort Wayne News-Sentinel, managed the city’s municipal airport, helped monitor and maintain safe skies above the continental United States during World War II, and directed Indiana’s first Aeronautics Commission.